System Theory in Geomorphology Challenges, Epistemological Consequences and Practical Implications - von Elverfeldt, Kirsten; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2012)
Empirical research needs a profound theory to be successful. This is the simple but, in its consequences, radical approach for this study in geomorphology. It critically analyses the current system understanding and offers a new view for a geomorphology that understands systems as being open but at the same time operationally closed, as self-organized, structure-building and potentially self-referential. Kirsten von Elverfeldt succeeds in designing a theoretical framework that sets new standards within Physical Geography. By using state-of-the-art concepts in system theory, it offers also new bridges to Human Geography as well as to other neighbouring disciplines. This book was awarded the Dissertation prize 2010 of the German Working Group in Geomorphology of the DGfG and the Hans Bobek-prize of the ÖGG (Austrian Geographical Society).
Part I: Problem areas -- First problem area: Coherence of basic assumptions and concepts -- Second problem area: Openness and determinacy -- Third problem area: The physical basis -- Fourth problem area: Equilibria -- Complexity and non-linearity -- Tentative conclusions in two steps -- Part 2: Consequences and implications -- Epistemological consequences -- Practical implications -- Meeting the challenge: An approach towards a geomorphological system theory -- Summary.
Keywords: Geography; Geology; Physical geography; Earth Sciences; Geomorphology; Physical Geography; Geography (general).